Sikh middle class, Panjabi cinema and the politics of memory. (2nd January 2018) - Abbi, Kumool
ABSTRACT: The paper attempts to look at the relationship between memory and politics in Panjabi cinema and its implications for the construction of Sikh identity, specifically through the prism of the Sikh Middle Class. It seeks to understand the manner in which this middle-class grapples with the memory of Operation Bluestar and 1984 riots, how this memory is recreated in the present and how it continues to reside as contemporary in individual consciousness. To do so, it attempts to understand the popularity of recent films dealing with Sikh militancy and also to contextualize the present period in which these films have become very relevant to both the local and diasporic audiences, in particular, the way in which people connect to Operation Bluestar and Delhi riots almost 30 years after the event.